THE CULTURAL PRESERVATION OF PIIL PESINGGIRI IN LAMPUNG MULITICUTURAL SOCIETY: CITIZENSHIP EDUCATION STUDY IN BARADATU, WAYKANAN - Prayoga Bestari, Edi Siswanto, Astim Riyanto (Jurnal Civicus, 2014)
This study describes the cultural preservation efforts of Piil Pesinggiri as indigenous Lampung people diitinjau of Civics as socio-cultural dimensions that include various forms of social and cultural behavior. Based on the data analysis can be understood that the preservation of culture in society mulitikutural Piil Pesinggiri Lampung done through some of cultivate action early on to children or future generations, provide socialization to the community about the significance of cultural values Piil Pesinggiri, which cooperates intense well with other traditional leaders or outside the community that is in Lampung with the government to provide socialization, as well as cultivate a culture Piil Pesinggiri in Lampung society.